2022
DOI: 10.3390/buildings13010075
|View full text |Cite
|
Sign up to set email alerts
|

Shear Strength of Concrete Beams without Stirrups Made with Recycled Coarse Aggregate

Abstract: Eco-friendly concrete that considers waste material and requires less energy for production is in demand because it produces less carbon dioxide, reduces the consumption of raw material, and can be a cheaper option to conventional concrete. The objectives of this study are to investigate the shear behavior of reinforced concrete beams made with locally produced recycled coarse aggregate from construction demolition waste, study the important parameters that affect the shear strength and ductility, and check th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…The experimental test results demonstrate that the tensile strength of pervious concrete drops from 1.56 MPa when natural aggregate is used to 0.67 MPa when recycled aggregate is used. Although concrete employing recycled aggregate is expected to be weaker in tension when compared with concrete containing natural aggregate, the observed drop is much more drastic when compared with previous studies by the authors [56][57][58][59][60][61] on non-pervious concrete. The inferior quality of the recycled coarse aggregate due to its higher water absorption, lower density, possible content of organic substances, higher level of crushability, and reduced abrasion resistance contributes to lower tensile strength of pervious concrete.…”
Section: Split Tensile Strengthcontrasting
confidence: 56%
See 1 more Smart Citation
“…The experimental test results demonstrate that the tensile strength of pervious concrete drops from 1.56 MPa when natural aggregate is used to 0.67 MPa when recycled aggregate is used. Although concrete employing recycled aggregate is expected to be weaker in tension when compared with concrete containing natural aggregate, the observed drop is much more drastic when compared with previous studies by the authors [56][57][58][59][60][61] on non-pervious concrete. The inferior quality of the recycled coarse aggregate due to its higher water absorption, lower density, possible content of organic substances, higher level of crushability, and reduced abrasion resistance contributes to lower tensile strength of pervious concrete.…”
Section: Split Tensile Strengthcontrasting
confidence: 56%
“…The tests showed that 100% replacement of the aggregate caused the compressive strength of pervious concrete to reduce by 36%, from 7.08 to 4.53 MPa. Earlier studies by the first two authors [56][57][58][59][60][61] on non-pervious concrete have indicated the full replacement of natural coarse aggregate with recycled aggregate from construction demolition waste obtained from the same source can reduce the compressive strength by an average of just 10-15%. The lack of adequate amount of fine aggregate in pervious concrete increases the importance of the coarse aggregates and the bond between them to the mechanical properties of the concrete.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…This improved result of the R-M-100 mix can be attributed to the rough texture of the RA, which enhances the interlocking action within the concrete. This interlocking effect contributes to an improved tension behavior in concrete containing RA [31]. The presence of such surface characteristics in the RA can create a more efficient stress transfer mechanism, resulting in the observed increase in tensile strength.…”
Section: Fresh and Hardened Concrete Propertiesmentioning
confidence: 97%
“…Most of the available research on the shear behavior of structural concrete made with recycled aggregate suggests that beams made with RA concrete possess either just about the same or marginally inferior ultimate shear strength compared to corresponding beams made with NA concrete. Table 2 summarizes some of the related research efforts found in the literature [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Performance Of Concrete Structures Prepared With Ramentioning
confidence: 99%
“…Odero et al [21] tested sixteen concrete beams using RCA and concluded that at 10 mm aggregates, the shear capacity of the specimens was at its highest by 21.5%. Sagheer et al [22] had tested fifteen concrete beams with 50 % RCA for some and 100 % RCA for the others. The specimens with 100 had a 26% increase in their shear capacity compared to the 50 % RCA.…”
Section: Introductionmentioning
confidence: 99%